4-(1-Methylethyl)-N-((E)-4-{[1-(prop-2-en-1-yl)-1H-1,2,3-triazol-4-yl]methoxy}benzylidene)aniline - Akkurt, Mehmet (International Union of Crystallography, 2013)
In the title compound, C(22)H(24)N(4)O, the terminal and central benzene rings make dihedral angles of 52.7 (3) and 43.8 (2)°, respectively, with the triazole ring. The dihedral angle between the benzene rings is 8.9 (2)°. The crystal structure features C—H⋯π interactions. The atoms of the terminal propenyl group are disordered over two sets of sites, with a refined occupancy ratio of 0.714 (14):0.286 (14).